Integrated Water Management Decision Support System for Seberang Perak Paddy Estate - Mohamed Najim, Mohamed Mujithaba (2004)
A study was carried out to develop an integrated water management decision support system for the Seberang Perak paddy estate. The decision support system incorporated results from a database management system, a model base management system and a rule based knowledge base system.